PENGARUH PENEMPATAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA KARYAWAN PADA PT. BRI (PERSERO), TBK CABANG SEMARANG PATTIMURA - Elizabeth Febrianti Widianingsih; Saryadi Saryadi; Reni Shinta Dewi (Jurnal Ilmu Administrasi Bisnis, 2014)
This research purpose to find out the effect of placement and compensation on employee performance through employee satisfaction remains at PT. BRI branch Pattimura Semarang. This type of research is explanatory. The number of samples taken were 47 respondents to the purposive sampling method with the criteria of all permanent employees. Collecting data using questionnaires, interviews, library research. Hypothesis testing using statistical analysis includes correlation coefficient, coefficient of determination, t-test, and F test results of this study show that employment has no effect on job satisfaction of 25.2%, while the compensation has no influence on job satisfaction, job placement has influence on employee performance by 19.2%, compensation has an influence on the performance of employees by 8.8%, and job satisfaction affects the employee's performance of 38.1%. Then the job placement and compensation together have an influence on job satisfaction at 34.2%, and job placement, compensation, and job satisfaction jointly affect the performance of 52.2%.